Effects of working memory on naturally occurring cravings. (November 2019) - Dodds, Chris M.; Magner, Bella; Cooper, Emily; Chesterman, Tara; Findlay, Sophie
Abstract: Elaborated Intrusion (EI) theory posits a key role for visuospatial working memory (WM) in craving. In line with the predictions of EI theory, several studies have found that WM and craving show mutually interfering effects - for example, performance of visuospatial WM tasks has been found to attenuate naturally occurring cravings. However, the extent to which these effects are driven specifically by visuospatial processing remains unclear. We conducted two experiments to investigate the effects of WM on naturally occurring cravings in more detail. In experiment 1, we examined whether such effects are driven specifically by visuospatial WM processes or can also be induced by a verbal WM task. Subjective craving ratings were attenuated equally by performance of visuospatial and verbal WM tasks, suggesting that craving is not dependent specifically on visuospatial processing. In experiment 2, we examined whether effects of visuospatial WM on craving could be driven by simple distraction. Naturally occurring cravings were attenuated in a control condition with minimal WM demands (watching a video). However, the magnitude of attenuation was significantly greater in a visuospatial WM condition. Taken together, these findings highlight a key role for WM in the attenuation of naturally occurring craving, but do not support the hypothesis that such effects are dependent specifically on visuospatial processing. Highlights: Performance of a working memory task reduces naturally occurring cravings. Attenuation of ratings occurs equally for visuospatial and verbal working memory. Working memory is more effective than simple distraction at reducing craving.